ANALISIS LITERASI DIGITAL PESERTA DIDIK PADA PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR NEGERI LARANGAN SELATAN 1 - Bintang Senja Riduan; Lutfi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the still-low level of digital reading literacy among elementary school students in Indonesian language instruction, despite the implementation of digital technology. This study aims to describe the level of digital reading literacy among fifth-grade students, identify the factors influencing it, and describe the use of digital learning resources in Indonesian language instruction at SDN Larangan Selatan 1. This study employs a qualitative approach using the case study method. Data collection was conducted through observation, semi-structured interviews, and document analysis, with the research subjects being two fifth-grade teachers and four students. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that students’ digital reading literacy falls into the “fairly good” category. Students are able to follow and understand digital texts, but still face limitations in critically evaluating and utilizing digital information. Factors influencing digital reading literacy include supporting and inhibiting factors. Supporting factors are technological factors and reading-related factors, while inhibiting factors are individual ability and ethical considerations regarding the use of digital media. Digital learning resources have been utilized quite effectively in Indonesian language instruction. Teachers use digital texts to present reading materials, assign summary tasks, ask comprehension questions, and provide follow-up activities that engage students in critical thinking. The findings of this study underscore the importance of strengthening digital reading literacy through well-planned instructional strategies and the effective use of digital media in Indonesian language instruction at the elementary school level.